Traditional Knowledge on the Intellectual Property of the Indigenous People of Tenganan Pegringsingan Bali - Kuspraningrum, Emilda; Flambonita, Suci; Cholil, Yuliati (Arena Hukum, 2025)
The potential of traditional knowledge of the indigenous people of Tenganan Pegringsingan, Manggis District, Karang Asam Regency, Bali, leads readers to a new insight that this potential can be measured through the concept of Intellectual Property Rights. This is in accordance with the parameters listed in WIPO and the mandate of Government Regulation No. 56 of 2022 concerning Public Intellectual Property. However, this potential has not been identified as an intellectual property right. This article explores the diverse traditional wisdom within the indigenous community of Tenganan that potentially has an intellectual property right. This traditional wisdom is recorded as part of the knowledge in the Intellectual Property Rights regime using a proprietary system. This study employs a qualitative method with hermeneutic analysis to explore the traditional wisdom of the indigenous people of Tenganan and its potential for protecting intellectual property rights. The results of this study aim to identify the traditional knowledge of the Tenganan indigenous community and classify it within the intellectual property rights regime as regulated in Indonesia’s Intellectual Property Rights Law, with the expectation of supporting the communal intellectual property of the Tenganan people.